(3GdedGMI aj Yde GdadGMIs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s; (3GdQVj GdZRj , eMeO Hf eMeO Hf CMeO Hf YHO Gddg GdYGeQj, QVj GdOjf CHh GdaVd,J (B935 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ HYHOGdZfi s
(3BNQgG (B:s
(3hQO MSf dhfg hQjMg hefY aSGQg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdRQGYI h GdCYTGHs